OPTIMIZATION OF UKRAINIAN ECONOMY STRUCTURE - BOBROVYTSKYI, Anatolii (Ekonomichna ta Sotsialna Geografiya, 2015)
The structure of the economy is a key indicator of its development Research trends changes in the structure is the subject of many studies of western and domestic researchers to accelerate and optimize the development of the economies , increase their competitiveness and tracking global development processes. The publication is dedicated to the process of tracking changes in the structure of Ukraine’s economy and forecasting of medium- and long-term prospects of its development within the framework of integration into the world economic space. Detailed attention is devoted to the prediction of each of the key economic sectors of Ukraine.

Структура економіки країни є ключовим показником її розвитку. Дослідження тенденцій змін структури є предметом багатьох досліджень західних та вітчизняних дослідників для прискорення та оптимізації розвитку економік, підвищення їх конкурентності та відслідковування глобальних процесів розвитку. Публікація присвячена відстеженню процесу зміни в структурі економіки України та середньо і довгострокового прогнозування перспективи її розвитку в рамках інтеграції в світовий економічний простір. Детальна увага присвячена прогнозуванню розвитку кожного з ключових секторів економіки України.
ОПТИМІЗАЦІЯ СТРУКТУРИ ЕКОНОМІКИ УКРАЇНИ
Keywords: economy structure; main sectors of national economy; industrial sector; services; agro-sector; branch structure of economy; territorial structure of economy; структура економіки; основні сектори економіки; промисловий сектор; сектор послуг; сектор сільського господарства; галузева структура; територіальна структура